2012
DOI: 10.4103/0019-557x.106419
|View full text |Cite
|
Sign up to set email alerts
|

Screening for thalassemia and other hemoglobinopathies in a tertiary care hospital of West Bengal: Implications for population screening

Abstract: Hemoglobinopathies are common genetic disorders of hemoglobin, which can be prevented by population screening and offering genetic counseling. In absence of population-based screening for hemoglobinopathies, the hospital-based diagnosis register provide idea about the extent of problem in the community. The present study was undertaken to find out the burden of hemoglobinopathies and spectrum of this disorders among the population who were screened in the hospital-based screening program. A record-basedanalysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 1 publication
4
18
1
1
Order By: Relevance
“…Sachdev et al [26] , Jain et al [30] and Mukhopadhyay et al [29] found 12.57%, 29.3 % and 14.5% abnormal hemoglobin fractions respectively. Sachdev et al [26] , Rao et al [27] , Dolai et al [28] and Mukhopadhyay et al [29] found beta thalassemia trait cases to be 8.9 %,18.1 %,10.38 % and 5.6 % respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Sachdev et al [26] , Jain et al [30] and Mukhopadhyay et al [29] found 12.57%, 29.3 % and 14.5% abnormal hemoglobin fractions respectively. Sachdev et al [26] , Rao et al [27] , Dolai et al [28] and Mukhopadhyay et al [29] found beta thalassemia trait cases to be 8.9 %,18.1 %,10.38 % and 5.6 % respectively.…”
Section: Discussionmentioning
confidence: 95%
“…It was also detected to be the most common type of thalassemia in a similar study in Bangladesh by Uddin et al 3 Studies of pattern of hemoglobinopathies in West Bengal in India also found Hb Eβ thalassemia to be the most common type of thalassemia. [4][5][6] Hemoglobin E β thalassemia shows a varied presentation from a mild type of thalassemia to severe type like beta thalassemia major. 7,8 β thalassemia major was the second most common type of thalassemia seen.…”
Section: Discussionmentioning
confidence: 99%
“…3 while it was found in 1.07%, 0.2% and 3.67% in three studies in Eastern India. [4][5][6] HbS gene is mainly seen in Central India like Maharashtra, Madhya Pradesh and Gujarat while it is rare in other states of India. 9 Hb S gene is characterized by replacement of glutamine to valine at position 6 of beta globin chain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations